Pelatihan Penyusunan Akad-akad bagi Pengurus dan Karyawan BMT Amanah Madinah Ngeni Waru Sidoarjo - Abdul Wahab (Lembaga Pengembangan Kinerja Dosen, 2025)
Baitul Mal Wattamwil (BMT) is a microfinance institution in its operations based on sharia principles, its existence is very strategic for the development of micro businesses that are not touched by the services of commercial banks both conventional and sharia, because they are less bankable. . BMT Amanah Madinah, which is located in Ngeni Village, Waru Subdistrict, Sidoarjo Regency, has been serving micro entrepreneurs in helping with capital. These services make BMT Amanah Madinah continue to improve for the better. One form of improvement is the holding of training in the preparation of sharia contracts for administrators and employees. The hope is that after the training the management and employees will be able, understand and apply it in daily practice, so that the contracts used are in accordance with sharia. the purpose of this activity is to improve the ability of BMT administrators and employees in the preparation of sharia contracts that are in accordance with customer needs and their application in daily practice. The training program for the preparation of contracts for administrators and employees of Baitul Mal Wattamwil (BMT) Amanah Madinah Waru Sidoarjo, was carried out well and smoothly according to plan, and most participants were able to receive the material well. Participants were enthusiastic about the activities as indicated by the liveliness of the participants in the activity process.